Exploring the fate of liposomes in the intestine by dynamic in vitro lipolysis - Parmentier, Johannes; Fricker, Gert (International journal of pharmaceutics, 2012)
Liposomes are generally well tolerated drug delivery systems with a potential use for the oral route. However, little is known about the fate of liposomes during exposure to the conditions in the gastro-intestinal tract (GIT). To gain a better understanding of liposome stability in the intestine, a dynamic in vitro lipolysis model, which so far has only been used for the in vitro characterisation of other lipid-based drug delivery systems, was applied to different liposomal formulations. Liposome size and phospholipid (PL) digestion were determined as two markers for liposome stability. In addition, the effect of PL degradation on the ability to maintain liposomally incorporated danazol in solution during lipolysis was evaluated in order to address the feasibility of liposomes designed for oral administration. Rate and extend of hydrolysis of PLs mediated by pancreatic enzymes was determined by titration and HPLC. Size of liposomes was determined by dynamic light scattering during incubation in lipolysis medium (LM) and during lipolysis. SPC-based (soy phosphatidylcholine) liposomes were stable in LM, whereas for EPC-3-based (hydrated egg phosphatidylcholine) formulations the formation of aggregates of around 1μm in diameter was observed over time. After 60min lipolysis more than 80% of PLs of the SPC-liposomes were digested, but dependent on the liposome concentration only a slight change in size and size distribution could be observed. Although EPC-3 formulations did form aggregates during lipolysis, the lipids exhibited a higher stability compared to SPC and only 30% of the PLs were digested. No direct correlation between liposome integrity assessed by vesicle size and PL digestion was observed. Danazol content in the liposomes was around 5% (mol/mol danazol/total lipid) and hardly any precipitation was detected during the lipolysis assay, despite pronounced lipolytic degradation and change in vesicle size. In conclusion, the tested dynamic in vitro lipolysis model is suitable for the assessment of liposome stability in the intestine. Furthermore, liposomes might be a useful alternative to other lipid based delivery systems for the oral delivery of poorly soluble drugs.